Digital storytelling: An innovative teaching method for medical education - Erwin Handoko; Wilvia Wilvia; Putranto Manalu; Yeni Halim; Nadya Nazimuddin Putri; Desi Novianti (Prima Journal of Oral and Dental Sciences, 2023)
Introduction: The transition from face-to-face to entirely online or hybrid teaching during the COVID-19 pandemic has been reported to reduce student engagement and lack of engagement among medical students. These changes require Medical educators to try innovative teaching methods to increase student engagement and improve medical teaching. Digital storytelling can potentially improve student engagement and provide a better learning experience for medical students. Methods: Narrative review of literature on digital storytelling and Medical education. Discussion: Digital storytelling is a multistep process. Planning and creating a digital story has effectively improved self-reflection, literacy, communication, idea organization, and technology skills. Conclusion: Using digital storytelling could be a valuable addition to teaching methods in Medical schools. Adopting this innovative teaching method could provide a better learning experience for medical students.